The Role of Microinsurance in Helping Industrial Enterprises (MSME) in Indonesia - Lesar, WIlilam Stephanus Tristan Lesar; Iriani, Ririt (Journal of Economics, Business, and Government Challenges, 2024)
This journal discusses a number of key aspects regarding the role of microinsurance in driving industry development. First, microinsurance provides financial protection to micro and small businesses, which are often the backbone of the industrial sector in Indonesia. This protection helps reduce the risks associated with business failures and losses due to disasters or other unforeseen events. Second, microinsurance encourages investment and innovation in industrial sectors by providing a sense of security to entrepreneurs. This can accelerate the growth and diversification of domestic industries, which in turn can create jobs and increase productivity.Overall, this journal concludes that microinsurance has a significant role in supporting industrial development in Indonesia. By providing protection and financial support to micro and small businesses, microinsurance has the potential to become a driver of sustainable and inclusive economic growth in the country. However, collaborative efforts from the government, financial institutions and the private sector are still urgently needed to maximize the benefits of microinsurance for the development of Indonesian industry.